UV-treated graphene oxide as anode interfacial layers for P3HT : PCBM solar cells. (23rd June 2015) - Cheng, Cheng-En; Tsai, Cheng-Wei; Pei, Zingway; Lin, Tsung-Wu; Chang, Chen-Shiung; Chien, Forest Shih-Sen
Abstract Solution-processable graphene oxide (GO) ultrathin films were introduced as anode interfacial layers (AILs) for polymer solar cells (PSCs). The photovoltaic performance of PSCs containing thermal- and UV-treated GO was comparable to that of PSCs with conventional poly(3, 4-ethyledioxythiphene):poly(styrenesulfonate) AILs. UV treatment induced the surface activation of GO; an increase in the work function of UV-treated GO improved the energy band alignment at the GO/poly(3-hexylthiophene) interface, which accounted for the efficient hole collection and photovoltaic performance of PSCs with treated GO.